Stolen - Ayala, Violeta; Fallshaw, Dan (Australia, 2009)
The documentary follows a Saharawi refugee separated from her mother, since she was a toddler, and reunited through a UN family reunion program. The reunion reveals a secret and the film quickly spirals into another world where nobody is as they seem.
Verzio Film Festival Submission
Keywords: Documentary films